(untitled) (Texas Journal of Medical Science, 2026)
Globally, targeted scientific research is being conducted aimed at a deeper study of the origin and pathogenesis of renal dysfunction (RD), determining the role of Klotho protein in the mechanism of its development. This protein plays an important role in kidney function and the vascular system. A decrease in the amount of Klotho protein intensifies the pathological process in these systems. This study examines the relationship between Klotho protein and RD development.